Insulin Modulates Paracoccidioides brasiliensis-Induced Inflammation by Restoring the Populations of NK Cells, Dendritic Cells, and B Lymphocytes in Lungs - Felipe Beccaria Casagrande; Sabrina de Souza Ferreira; Fernanda Peixoto Barbosa Nunes; Lavínia Maria Dal’Mas Romera; Suelen Silvana dos Santos; Fernando Henrique Galvão Tessaro; Paula Regina Knox de Souza; Sandro Rogério Almeida; Joilson Oliveira Martins (Journal of Diabetes Research)
Paracoccidioidomycosis, a key issue for Brazilian health service, can be aggravated in patients with impaired immunological responses, such as diabetic patients. We evaluated the role of insulin in inflammatory parameters in diabetic and nondiabetic mice using a systemic mycosis Paracoccidioides brasiliensis (Pb) model. Diabetic C57BL-6 mice and controls were infected with Pb18 and treated with insulin for 12 days prior to experiments. After 55 days, infected diabetic mice exhibited fewer leukocytes in both peritoneal lavage fluid (PeLF) and bronchoalveolar lavage fluid and reduced secretion of interleukin- (IL-) 6 in lungs. In addition, diabetic mice presented a reduced influx of TCD4+ cells, TCD8+ cells, B lymphocytes, NK cells, and dendritic cells compared to control infected groups. Insulin treatment restored the leukocyte number in PeLF and restored the presence of B lymphocytes, dendritic cells, and NK cells in lungs of diabetic animals. The data suggest that diabetic mice present impaired immunological response to Pb18 infection and insulin modulates inflammation by reducing IL-6 levels in lung and CINC-1 levels in spleen and liver homogenates, restoring leukocyte concentrations in PeLF and also restoring populations of dendritic cells and B lymphocytes in lungs of diabetic mice, permitting the host to better control the infection.